Nationalism and the Multinational State (American Journal of Islam and Society, 1992)
We live in a world of nation-states where national cohesiveness constitutesthe legitimizing ground for political unity. In such a world, multinationalpolitical units are considered to be peculiar entities whose existence is eithertaken as an exception to the rule or is considered to be transient and thereforedestined to collapse into its national units.A product of Eutope’s historical experience, nationalism found its wayto the Muslim world and gained many adherents and advocates in its ethnic(i.e., Arabic, Turkish, Kurdish) and religious (i.e., Pakistani, Iranian) forms.The nationalistic mindset has become an intrinsic part of the political thinkingof many Muslim individuals and groups. As a result of the discontinuity inhistorical political thinking and practice effected by the European cultural andpolitical domination of Muslim life for the last two centuries, many Muslimsare unaware of the much superior political structutes which existed-albeitin rudimentary, distorted, or compromised forms-before Westem penetration.In this paper, I will discuss the origin and development of the concept ofnationalism, underscore its defects, and point out some of its devastatingconsequences, especially in regions rich in ethnic and religious minorities. Iargue that nationalism is a European phenomenon invented by German intellectualsand employed by Prussia in order to bring about a united Germanstate. I contend that a national govemment tends to suppress minority groupsand is therefore inappropriate to societies with heterogenous and diversepopulations. I conclude by discussing, in general terms, the model of communalpluralism that flourished under the khilafah system.The Genesis of NationalismNationalism is a relatively modem political doctrine. Writers on nationalismtrace it back to Rousseau, a European philosopher who insisted that agood political community was characterized by a homogeneous population.However, nationalism as we know it today began to take shape not in France,but in Germanic Prussia. German writers interested in a united German statebegan to advocate nationalism as the only legitimate basis for statehood ...